Large Kondo effect in assemblies of Au nanoparticles linked with alkanedithiol electron bridges. Issue 12 (8th March 2019) - Tie, Monique; Gravelsins, Steven; Niewczas, Marek; Dhirani, Al-Amin
Abstract : The controllable, functional architectures of nanostructures represent a target of opportunity as a versatile means for introducing localized, magnetic impurities (unpaired spins) and generating the Kondo effect in nanostructure assemblies. Abstract : Using a prototypical nanoparticle–molecule assembly, namely alkanedithiol-linked gold nanoparticle films, we observe hallmark signatures of the Kondo effect in conductance vs. voltage as well as temperature measurements. Its contribution to temperature dependence of conductance is much larger than those from all other temperature-dependant effects up to 300 K by >20-fold – much larger than previous reports of the Kondo effect using other platforms. We find that previous models of the Kondo effect describe our data even in this regime. Given the synthetic control available over nanoparticle properties such as surface area, shape, and chemical composition, our work points to combining flexibility afforded by molecule + nanoparticle assemblies as a powerful way to generate materials exhibiting strong spin–electron interactions.